As Catadoras de mangaba no Programa de Aquisição de Alimentos – PAA: um estudo de caso em Sergipe - MOTA, Dalva Maria da (Universidade Federal do Pará, 2018)
This article is about the experience of a group of women in the commercialization of gathered wild fruits through the governmental Food Purchase Program (PAA) in the Brazilian State of Sergipe. The analytical framework is associated to the debate on poverty and specific public policies for traditional communities in rural areas. The women hold a collective identity as the mangaba gatherers, based on their use of common pool resources with low environmental impact. They mobilize themselves through the MCM – Movimento das Catadoras de Mangaba, Mangaba Gatherer Women´s Movement. Although they have recently been recognized as having specific legal rights, they are experiencing the dwindling of the resources they gather, as well as difficulties in commercialization of the fruits due to their seasonality and the unpredictability of access. The research was carried out between 2008 and 2011 and involved direct and participant observations and open-ended interviews. The main results show that the PAA has contributed to increased income, consumption and self-esteem. There was a re-arrangement in their way of participating in the program, meanwhile some of their traditional practices were relegated. The program rules were re-signified and adapted locally. While growing solidarity has been observed among the gatherers, competition for the fruits has also increased.